(3JMQjQ cJGH aGfGdGhS aj GdCTcGd GdcQjIs
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI Cbhd HYO MeO Gddg Gfj cfJ CQjO Cf GMQQ GdcJH GdehSheI HGdeJhSWI CYfj GdcJH GdJj ef TCfgG Cf jJhSW aj GdJQjH GdJYdej s
(3BNQgG (B:s
(3hGdPj GOYGg aj UOQ GdTcd fSHI GdbhSjf dGfSHI GdMSjf s
(3Vef eLehY , JQJjHgG (B: 7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3eJaQbGJs